Reliability Of Accounting Information Reduces Financial Fraud According To The International Standard (ISA1) - Haidar Omran Al-Jaber; Mondher Fakhfakh (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
The research aimed to Highlighting the International Accounting Standard No (1) Presentation of financial statements and Identify the concept of reliability of accounting information and The nature of financial fraud and the extent to which it can be reduced through documented accounting information. The research problem was as follows from the fact that any lack or deficiency in the reliability of the accounting information for the financial statements will reduce the degree of reliance on them, which affects those lists prepared by financial institutions (banks) operating in Iraq that failure to take the standard of presentation of financial statements No (1) will inevitably lead to the lack of credibility and reliability of accounting information, which results in misleading accounting outputs that will be a door to financial fraud in its various forms Hence. the main research problem can be crystallized by the following question:  Will enhancing the reliability of accounting information in accordance with Financial Statement Presentation Standard No (1) reduce financial fraud?. The research reached many conclusions, the most important of which are - The accounting information is presented in the form of accounting reports prepared in accordance with an accounting system called financial reports, as these reports are the final product of the accounting system for any economic unit because of its role in supplying and providing stakeholders in the economic unit with information that contributes to economic decision-making and that financial reports are a means of informing external parties benefiting from various financial information about the activities of the economic units issued by them. - The honesty of accounting information, impartiality and objectivity make the financial statements and reports reliable and credible, enabling users of various orientations to rely on them in making any of the financial decisions.